Demonstration of Normally-Off Recess-Gated AlGaN/GaN MOSFET Using GaN Cap Layer as Recess Mask - Xu, Zhe; Wang, Jinyan; Liu, Jingqian; Jin, Chunyan; Yong Cai; Yang, Zhenchuan; Wang, Maojun; Min Yu; Xie, Bing; Wu, Wengang; Ma, Xiaohua; Zhang, Jincheng; et al. (IEEE ELECTRON DEVICE LETTERS, 2014)
Based on our proposed self-terminating gate recess etching technique, normally-off recess-gated AlGaN/GaN MOSFET has been demonstrated with a novel method using GaN cap layer (CL) as recess mask, which, as a result, simplifies the device fabrication process and lowers the fabrication cost. The GaN CL is capable of acting as an effective recess mask for the gate recess process, which includes a thermal oxidation for 45 min at 650 degrees C followed by 4-min etching in potassium hydroxide (KOH) at 70 degrees C. After gate recess process, no obvious change is observed in terms of the surface morphology of the GaN CL, the contact resistance of the Ohmic contact formed directly on the GaN CL as well as the sheet resistance of the two-dimensional electron gas (2-DEG) channel layer under the GaN CL. The fabricated device exhibits a threshold voltage (V-th) as high as 5 V, a maximum drain current (I-dmax) of similar to 200 mA/mm, a high ON/OFF current ratio of similar to 10(10) together with a low forward gate leakage current of similar to 10(-5) mA/mm. Meanwhile, the OFF-state breakdown voltage (V-br) of the device with gate-drain distance of 6 mu m is 450 V.